2020
DOI: 10.1111/nmo.13884
|View full text |Cite
|
Sign up to set email alerts
|

Application of metabolomics to the study of irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is diagnosed based on symptoms 1 and is the most commonly diagnosed bowel disorder. 2 While this symptom-based approach has the advantage of limiting unnecessary testing 3 compared with a "diagnosis of exclusion" approach, the gastrointestinal tract has a limited symptom repertoire. Consequently, this symptom-based diagnosis captures a large but heterogeneous patient population, with multiple pathophysiological mechanisms underlying symptoms. 4 Using the Rome IV criteria, IBS sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Reliable biomarkers to distinguish IBS from other gastrointestinal inflammatory diseases or to evaluate the progression of the disease are subject of research but remain elusive and still warrant further validation. 56,57 Our findings indicate that the measurement of serum GlycA levels may play a potential role within IBS diagnosis or monitoring and might indicate whether IBS patients are at increased risk for a severe course of disease. We recommend further investigation of its relation to IBS, especially the relation to IBS-D, in other larger cohorts, as we can only detect an association through our study, but not a causal link.…”
mentioning
confidence: 81%
“…Reliable biomarkers to distinguish IBS from other gastrointestinal inflammatory diseases or to evaluate the progression of the disease are subject of research but remain elusive and still warrant further validation. 56,57 Our findings indicate that the measurement of serum GlycA levels may play a potential role within IBS diagnosis or monitoring and might indicate whether IBS patients are at increased risk for a severe course of disease. We recommend further investigation of its relation to IBS, especially the relation to IBS-D, in other larger cohorts, as we can only detect an association through our study, but not a causal link.…”
mentioning
confidence: 81%
“…Large studies of microbiome composition by 16S rRNA gene sequencing or shotgun metagenomics have in some cases shown minimal diversity change and taxonomic associations with IBS, while others have reported reduced diversity and taxonomic shifts that were not consistent across studies [6][7][8][9][10]. Recent studies have shifted to focus on functional characterization of the microbiome by shotgun metagenomics, which assesses functional potential by microbial gene content, or metabolomics, which assesses products of bacterial metabolism detected in feces [7,[11][12][13][14][15][16]. While these studies have reported significant shifts in gene content and metabolites, the specific features have not been consistent across studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review has pointed on the absence of a common metabolomic profile in IBS patients. 17 Liu Y et al 18 found no significant differences in community structures between IBS and healthy controls at the amplicon sequence variants level. However, IBS has been differentiated from healthy controls at genus level by using machine learning approaches, and authors detected nine new microbiome biomarkers of IBS.…”
Section: Doing Better With Functional Gastrointestinal Disorders? Pro...mentioning
confidence: 96%
“…The significant heterogeneity among studies depends on different methods, sampling modality and geographical settings. A recent review has pointed on the absence of a common metabolomic profile in IBS patients 17 …”
mentioning
confidence: 99%